Expert Consensus Guidelines: How to safely perform minimally invasive anatomic liver resection. (29th November 2021) - Gotohda, Naoto; Cherqui, Daniel; Geller, David A.; Abu Hilal, Mohammed; Berardi, Giammauro; Ciria, Ruben; Abe, Yuta; Aoki, Takeshi; Asbun, Horacio J.; Chan, Albert C. Y.; Chanwat, Rawisak; Chen, Kuo‐Hsin; et al.
Abstract: Background: The concept of minimally invasive anatomic liver resection (MIALR) is gaining popularity. However, specific technical skills need to be acquired to safely perform MIALR. The "Expert Consensus Meeting: Precision Anatomy for Minimally Invasive HBP Surgery (PAM‐HBP Surgery Consensus)" was developed as a special program during the 32nd meeting of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery (JSHBPS). Methods: Thirty‐four international experts gathered online for the consensus. A Research Committee performed a comprehensive literature review, classifying studies according to the Scottish Intercollegiate Guidelines Network method. Based on the literature review and experts' opinions, tentative recommendations were drafted and circulated among experts using online Delphi Rounds. Finally, formulated recommendations were presented online in the Expert Consensus Meeting of the JSHBPS on February 23rd, 2021. The final recommendations were validated and finalized by the 2nd Delphi Round in May 2021. Results: Seven clinical questions were selected, and 22 recommendations were formulated. All recommendations reached more than 85% consensus among experts at the final Delphi Round. Conclusions: The Expert Consensus Meeting for safely performing MIALR has presented a set of clinical guidelines based on available literature and experts' opinions. We expect these guidelines to have a favorable effect on the safe implementation and development of MIALR. Abstract : Highlight Gotohda and colleagues report on the minimally invasive anatomic liver resection recommendations formulated in the Expert Consensus Meeting: PAM‐HBP Surgery Project held as a special program during the 32nd meeting of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery in February 2021 and finalized after a second Delphi round in May 2021.